Rice flakes muesli: A novel nutrient-dense gluten-free breakfast cereal - Itagi, Hameeda Banu; Gupta, Nitesh; Ong, Glenn Vincent; Pratap, Vipin; Roy, Priyabrata; Ramos-Castrosanto, Ana Rose; Singh, Vivek Kumar; Tiozon, Rhowell Navarro; Sreenivasulu, Nese (Elsevier, 2025)
Rice flakes muesli is a gluten-free, nutrient-dense cereal developed using Indian landrace rice flakes, pigmented popped rice, and nuts, offering a functional alternative to commercial wheat, corn, and oat-based mueslis. This study utilized geographical indication-tagged rice landraces to produce innovative breakfast cereal alternatives addressing growing gluten-free food demand. Two muesli variants—jaggery-sweetened and chocolate-based—were developed, delivering distinct nutritional advantages enriched with dietary fiber, protein, essential minerals (iron, zinc, magnesium, copper, manganese), and elevated B-vitamins. The chocolate muesli provides 415.51 kcal per 100g, meeting 19.57 % of daily fiber needs and 9.74g protein, with significant mineral content including iron (68.33 mg/kg), zinc (21.86 mg/kg), and magnesium (1786.37 mg/kg), fulfilling up to 42.52 % of the daily requirement. The jaggery variant delivers 400.89 kcal per 100g, with 12.36 % fiber, and exceptional antioxidant properties, including total flavonoids (143.68 mg CE/100g), radical-scavenging activity (95.33 %), and FRAP value (8.48 mM/g). Both variants significantly contribute to daily mineral and fiber intake. Sensory evaluation using a 9-point hedonic scale with 26 semi-trained panelists revealed strong consumer preference for both formulations over a commercial option. The combination of gluten-free muesli variants with superior nutritional value and antioxidant-rich components exhibit appealing sensory characteristics, hence positions these products competitively in the functional food market, meeting needs of health-conscious consumers.